Stock market spillovers via the global production network: Transmission of U.S. monetary policy - Julian Di Giovanni; Galina Hale (Federal Reserve Bank of New York, 2020)
We quantify the role of global production linkages in explaining spillovers of U.S. monetary policy shocks to stock returns of fifty-four sectors in twenty-six countries. We first present a conceptual framework based on a standard open-economy production network model that delivers a spillover pattern consistent with a spatial autoregression (SAR) process. We then use the SAR model to decompose the overall impact of U.S. monetary policy on stock returns into a direct and a network effect. We find that up to 80 percent of the total impact of U.S. monetary policy shocks on average country-sector stock returns is due to the network effect of global production linkages. We further show that U.S. monetary policy shocks have a direct impact predominantly on U.S. sectors and then propagate to the rest of the world through the global production network. Our results are robust to controlling for correlates of the global financial cycle, foreign monetary policy shocks, and to changes in variable definitions and empirical specifications.
Keywords: G15; F10; F36; 330; global production network; asset prices; monetary policy shocks